Contribuição para o estudo da besnoitiose bovina em Portugal. - Cortes, Helder (2003)
Bovine besnoitiosis is a parasitic disease caused by the protozoa Besnoitia besnoiti (Marotel, 1912) that presents an acute phase (with fever and anasarca) and a chronic phase (with sclerodermitis), and has been characterized by high morbidity and low mortality (Ferreira, 1985). A study on the presence of besnoitiosis was carried out in October 2001 on a beef cattle herd located in the Évora region. On this farm, where previous cases of besnoitiosis were diagnosed, 12 assymptomatic Limousine bulls, aged between 18 and 24 months, were randomly selected and studied. Skin biopsies were collected and prepared. Subsequent histopathologic analyses of the biopsies have shown that 5 (42%) of the animals studied harboured B. besnoiti cysts. Therefore, these results demonstrate the immediate need to obtain insight in to some as yet not clearly defined aspects of the physiopathogeny of this disease. Possible ways of transmission (that is, determination of intermediate as well as definite hosts) and their impact on animal production such as bovine fertility and the quality of skins for leather industry should be addressed. In addition, the cases of assymptomatic animals with B. besnoiti in the Évora district should be clarified.